Intermediate Algebra

Combine like terms:
-3x^2+2x-4x^2-9+6x-2x^2+8

Solve for x:
8x-11= -11x+18

Solve for x:
-2(x-5)+7=z-8-5x

Solve for x:
(x-2)/5 - 3/2= (x+1)/10

Translate to an algebra statement; do not solve:
Seven times the difference of six and a twice a number yields the same result as the same number decreased by one.

  1. 👍 0
  2. 👎 0
  3. 👁 366
  1. I will be happy to critique your work. To solve for x, combine the terms that include x on one side and the constants on the other.

    "Combining" like terms" means separately combining the terms with different powers of x, and the constants.

    1. 👍 0
    2. 👎 0
  2. Seven times the difference of six and a twice a number yields the same result as the same number decreased by one.

    How does this translate into a algebra statement?

    1. 👍 0
    2. 👎 0
  3. I can answer 3x^2+2x-4x^2-9+6x-2x^2+8

    first you want to combined all the squared problems whch is : 3x^2 -4x^2-2x^2
    Since two negatives make a positive : 3x^2-4x^2 =7x^2
    now subtract -2x^2 and that leaves for 5x^2

    Now you combine all the numbers with variables : 2x +6x = 8x
    so now we have
    5x^2+ 8x

    now we combine all the constant numbers -9+8= -1

    answer 5x^2+8x -1

    1. 👍 0
    2. 👎 0
  4. 7(6-x2) = x2-1

    1. 👍 0
    2. 👎 0
  5. Seven times the difference of six and a twice a number yields the same result as the same number decreased by one.

    1. 👍 0
    2. 👎 0
  6. xlhn vkhbdo auzhfcgtm brexcg unsa mzagvc tbfjrec

    1. 👍 0
    2. 👎 0
  7. The ratio of 7 more than a number to 2 less than that number is 13/4. Find the number

    1. 👍 0
    2. 👎 0
  8. seven less than twice an unknown number

    1. 👍 0
    2. 👎 0

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math

    solve the equation 1. y-5/3=1 a) -2

    asked by Anonymous on December 18, 2015
  2. How do I do this.?(Math.)

    Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve one of the equations for x or y. Let's solve the first one for y: y - 2x = -5 y = 2x - 5 Now let's substitute 2x - 5 for y in the second

    asked by Margie on February 5, 2007
  3. Algebra

    To solve the system of equations, which expression could be substituted for x into the first equation? 3x-5y=14 x+4y=10 a)10-4y b)4y+10 c)(1/4)x+(5/2) d)(-1/4)x+(5/2) I have another problem just like this one so if you could

    asked by maddie on July 27, 2007
  4. Substitution Method-Plz help

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get

    asked by Svetlana on October 17, 2006
  5. algebra

    2a+3b-4c=7, a-b+2c=6 a) find an ordered triple of numbers (a,b,c) that satisfies both equations b) can you find a second ordered triple that satisfies both equations c) solve for b in terms of a, and solve for c in terms of a. how

    asked by Anonymous on August 2, 2019
  1. Math

    1. Which ordered pair is a solution of the equation y = −11x + 4? a. (0, -7) b. (-1, -7) c. (1, -7) d. (2, 26) MY ANSWER: C Because (X,Y) so -11x = -11 * 1 = -11 -11 + 4 = -7 2. A plumber charges $65 per hour to fix a leak. What

    asked by Sp on September 18, 2017
  2. Algebra

    There are 4 problems that I don't understand how to solve so, please help me. A numerical explanation with words explanation would be nice. Thank you tutors. Rewrite each equation so it is in the form ax + b = c or x + d/e = f,

    asked by anon on December 9, 2015
  3. ALGEBRA 1!PLZ HELP!

    Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve the first equation for y. y = 2x-5 Substitute that for y in the second equation and solve for x. Then use the value of x to substitute back

    asked by SANDRO! on November 6, 2006
  4. Algebra-please check my answers

    Solve the equation by expressing each side as a power of the same base and then equating exponents. 9^(x - 9)/8= sqrt of 9 i got 13 4^(x + 10) = 8^(x - 6) i got 38 Solve the exponential equation. Express the solution set in terms

    asked by Ang on October 26, 2007
  5. algebra

    solve for the indicated variable: a. temperature formula solve for F: K=5/9(F-32)+273 b. annual interest rate solve for R: A=P+Prt

    asked by narmin on September 24, 2009
  6. math

    What is the first step in solving the linear system {2x − 3y = 11 {−x + 5y = −9 by the substitution method in the most efficient way? A. Solve the first equation for x. B. Solve the first equation for y. C. Solve the second

    asked by math on March 31, 2020

You can view more similar questions or ask a new question.